When does the price affect the taste? Results from a wine experiment - Johan Almenberg; Anna Dreber (Stockholm School of Economics, The Economic Research Institute (EFI), 2009)
We designed an experiment that examines how knowledge about the price of a good, and the time at which the information is received, affects how the good is experienced. The good in question was wine, and the price was either high or low. Our results suggest that hosts offering wine to guests can safely reveal the price: much is gained if the wine is expensive, and little is lost if it is cheap. Disclosing the high price before tasting the wine produces considerably higher ratings, although only from women. Disclosing the low price, by contrast, does not result in lower ratings. Our finding supports the notion that price not only serves to clear markets, it also serves as a marketing tool; it influences expectations that in turn shape a consumer's experience. In addition, our results suggest that men and women respond differently to attribute information concerning wine.
Keywords: C91; D03; D83; M31; 330; Price-Quality Heuristic; Attribute Information; Role of Expectations; Marketing; Blind Tasting; Wine; Wein; Preis; Produktqualität; Erwartungstheorie; Konsumentenverhalten; Test; USA